Ionospheric Remote Sensing with GNSS - YuXiang Peng; Wayne A. Scales (Encyclopedia, 2021)
The Global Navigation Satellite System (GNSS) plays a pivotal role in our modern positioning, navigation and timing (PNT) technologies. GNSS satellites fly at altitudes of approximately 20,000 km or higher. This altitude is above an ionized layer of the Earth’s upper atmosphere, the so called “ionosphere”. Before reaching a typical GNSS receiver on the ground, GNSS satellite signals penetrate through the Earth’s ionosphere. The ionosphere is a plasma medium consisting of free charged particles that can slow down, attenuate, refract, or scatter the GNSS signals. Ionospheric density structures (also known as irregularities) can cause GNSS signal scintillations (phase and intensity fluctuations). These ionospheric impacts on GNSS signals can be utilized to observe and study physical processes in the ionosphere and is referred to ionospheric remote sensing. This entry introduces some fundamentals of ionospheric remote sensing using GNSS.